COUNSELING OF LOCAL FOOD AND GIVING SOCIAL ASSISTANCE TO MUZDALIFAH AND LYDIA ORPHANAGE - Choiriyah, Nurul Azizah; Iskandar, Zaldy; Sundjaja, Arya Putra; Dewi , Irra Chrisyanti; Rahmah, Latifahtur (ARDIMAS: Jurnal Arsip Pengabdian Masyarakat, 2021)
ABSTRACT Muzdalifah orphanage is a foundation that educates and cares for orphans aged 3 months-12 years. The Lydia orphanage focuses on developing elementary to high school children. The management and caregivers of the foundation are responsible for the health of foster children by providing nutritious food. The purpose of this community service wasto increase knowledge of local foodstuffs in increasing the body's immune system for the management of the Muzdalifah and Lydia orphanages also providing social assistance to meet the needs of orphans cared for by the two orphanages. Community service activities were carried out at the Muzdalifah orphanage, Jalan S Parman V No. 57A Waru, Sidoarjo, and the Lydia orphanage, Jalan Gayungsari V No. 17-21 Surabaya. Community service activities carried out are counseling on local foodstuffs to increase the body's immunity by using material modules and posters. The pre-test and post-test activities were carried out to Muzdalifah orphanage is a foundation that educates and cares for orphans aged 3 months-12 years. The Lydia orphanage focuses on developing elementary to high school children. The management and caregivers of the foundation are responsible for the health of foster children by providing nutritious food. The purpose of this community service wasto increase knowledge of local foodstuffs in increasing the body's immune system for the management of the Muzdalifah and Lydia orphanages also providing social assistance to meet the needs of orphans cared for by the two orphanages. Community service activities were carried out at the Muzdalifah orphanage, Jalan S Parman V No. 57A Waru, Sidoarjo, and the Lydia orphanage, Jalan Gayungsari V No. 17-21 Surabaya. Community service activities carried out are counseling on local foodstuffs to increase the body's immunity by using material modules and posters. The pre-test and post-test activities were carried out to measure increased knowledge of local food material that can increase body immunity. Based on the results of the pre-test and post-test, the knowledge of the board and caretakers of the foundation increased after counseling on local foodstuffs was held. The percentage of increased knowledge is 67-77%. Social assistance provided by the servant to foster children includes diapers, staple foodstuffs, and hygiene needs. Community service activities went on smoothly. The board of the orphanage was enthusiastic about participating in the counseling. Foster children also feel happy with the hospitality that has been done and the assistance provided. Keywords: immunity, local food, counseling, vitamins